The dissolution behaviour of titanium oxide phases in synthetic Bayer liquors at 90 C - Chester, Ryan; Jones, Franca; Loan, Mitch; Oliveira, Allan; Richmond, William (Elsevier, 2009)
Many of the bauxites currently being processed to alumina contain titanium minerals, yet little fundamental knowledge is available regarding their dissolution behaviour in Bayer liquors. In this paper the dissolution of various titanium oxide phases (anatase, rutile, sodium titanate and calcium titanate) are presented. It is shown that rutile, calcium titanate and sodium titanate have the expected dissolution behaviour, which increases with free caustic concentration. Anatase, too, generally increases in dissolution with free caustic concentration. However, anatase is shown to have an anomalous behaviour when gibbsite co-precipitates. In this case, the dissolution of anatase does not follow the expected free caustic trend. According to the data presented, the most probable cause is an impervious aluminium/sodium titanate surface layer hindering further dissolution.